Detection of ACCSuT, BLEE and AmpC resistance phenotypes in salmonella enterica strains isolated from infections in animal - Centeno S., David (2018)
The aim of this study was to detect the presence of resistance profiles, ESBL (Extended Spectrum Betalactamases), AmpC (AmpC Betalactamases) and ACSSuT phenotype (resistance to oxytetracycline, ampicillin, streptomycin, sulfatrimetropim, and chloramphenicol) in Salmonella enterica isolates by using the Kirby Bauer technique. Fifty isolates of Salmonella enterica identified according to ISO standard: 6579 (2002) were taken from the Laboratory of Microbiology of the Faculty of Veterinary Medicine of the National University of San Marcos. Twenty antibiotics of relevance in human and veterinary medicine were used. The results showed that 96% (48/50) of the isolates were resistant to at least one antibiotic. The highest frequencies of resistance were presented to chloramphenicol (94%), tobramycin (72%) and oxytetracycline (49%). Low resistance was observed in aztreonam (5%), cephalosporins (2-7%), sulfatrimethoprin (4%) and gentamicin (2%), intermediate resistance to ciprofloxacin (4%) and a high sensitivity (100%) to amikacin. In addition, 2% of the isolates presented the BLEE resistance phenotype, 2% the AmpC type beta-lactamases and 2% the ACSSuT phenotype. The results highlight the importance of the information generated by the sensitivity tests and their fundamental use in the monitoring and detection of resistance patterns in Salmonella.